The overlap of the novel and the short story: A critical reading in two Jordanian novels The Sheikh sieve, and Diesel as a model (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The new novel is a mosaic of texts literary, and an interlaced narrative system, as it has opened up to literary texts of all kinds and genres, and all of this came due to the developments, , overlaps and changes in the centers texts of life.  Authority and the Jordanian novel did not live in isolation from these transformations, as it was affected by what was affected by international and Arab literature, To confirm that, this study came to address two novel models of the new Jordanian novels: The Sheikh and the Gherbal, and Diesel's novel In order to identify a literary phenomenon in the new Jordanian novel writing tracks, and how it overlaps with the art of the short story  The texts are numerous, and perhaps the art of the short story is one of the first arts that overlapped with it; The novel and the short story have common denominators in construction and formation.